Mortality rate of mental disorder trends in China from 2002 to 2020 - Li, Boxuan; Zhang, Guoshuang; Ma, Jing; Kang, Mingxiu (Frontiers in Psychiatry, 2022)
Background: The number of people with mental disorders is increasing in China, but there are few studies on the temporal trends and population distribution of mental disorder mortality. Methods: The mortality of mental disorders were derived from the China Health Statistics Yearbook published by the National Health and Family Planning Commission. Temporal trends in mortality were examined with a joinpoint regression using annual percent change (APC) and average annual percent change (AAPC). A Poisson regression model was utilized to test the population-level risk factors associated with the death of people with mental disorders. Results: The mortality of mental disorders in rural Chinese residents showed a decreasing trend from 2002 to 2020 (AAPC -2.06, 95% confidence interval [CI] -0.9 to -3.7). The mortality of mental disorders in urban Chinese residents declined between 2005 and 2011 (APC -13.00, 95% CI -21.1 to -4.1). The mortality rate of mental disorders has decreased for urban males with an APC of -2.71 (95% CI -4.6 to -0.7). Urban women showed an increase in mental disorder mortality from 2002 to 2005 and from 2012 to 2020 with APCs of 19.65 (95% CI 0.6 to 42.3) and 6.16 (95% CI 2.2 to 10.3), respectively. Age was a significant risk factor for mental disorder mortality (odds ratio 1.28, 95% CI 1.23 to 1.32). Conclusion: The dissemination of medical and health information, investment in medical and health resources, and the modification and optimization of regulations have led to a decrease in mental disorder mortality in China. It is vital to devote greater attention to elderly individuals suffering from mental disorders.